Pria 80 tahun dengan tumor ganas dinding dada: laporan kasus - Raissa Andi Soekrisno; Dewa Gde Mahiswara Sudiatmika; Elysanti Dwi Martadiani; Firman Parulian Sitanggang; Herman Suputra (Intisari Sains Medis, 2021)
Background: Malignant tumors that form in bone, soft tissue, or cartilage, are called sarcomas. Symptoms of these tumors vary, and may include shortness of breath, chest pain, and swelling around the tumor. Imaging such as X-rays and CT scans can be helpful, although imaging features of the few malignant chest wall tumors that are less specific, knowledge of the typical radiographic manifestations of these tumors can often make it easier for experts to differentiate between benign and malignant tumors and help lead to a more specific diagnosis.Case presentation: An 80-year-old man complains of a lump in the right chest. The results of laboratory tests showed anemia, decreased kidney function, and hypercalcemia. The CT scan of the thorax with contrast showed a solid mass in the right pleural cavity infiltrating the surrounding chest wall muscles, bilateral pneumonia, and osteolytic lesions on the spine suspected of being a metastatic process or spreading malignancy. The results of the biopsy showed a diffuse morphological appearance of immature plasma cells with an approach to the diagnosis of cutaneous infiltration plasma cell myeloma with a differential diagnosis of plasmablastic lymphoma.Conclusion: The results of X-ray imaging and CT scan of the thorax help narrow the differential diagnosis, where there is an image of a tumor on the chest wall with destruction of the surrounding bone and soft tissue and an image of infiltration into the pleura accompanied by multiple osteolytic images of the vertebrae. Assisted by a biopsy (anatomical pathology), the closest diagnosis in this patient is plasma cell myeloma chest wall.  Latar Belakang: Tumor ganas yang terbentuk pada tulang, jaringan lunak, atau kartilago disebut sarcoma. Gejala dari tumor ini bervariasi, dapat berupa sesak nafas, nyeri dada, dan pembengkakan pada sekitar tumor. Pencitraan seperti rontgen dan CT scan dapat membantu, walaupun gambaran pencitraan dari beberapa tumor ganas dinding dada kurang spesifik, pengetahuan tentang manifestasi tipikal pada radilogi dari berbagai tumor ini seringkali dapat memudahkan para ahli untuk membedakan jenis tumor jinak dan ganas dan membantu mengarahkan diagnosis yang lebih spesifik.Kasus: Seorang laki – laki berusia 80 tahun dengan keluhan benjolan di dada sebelah kanan. Hasil pemeriksaan laboratorium didapatkan hasil anemia, penurunan fungsi ginjal, dan hiperkalsemia. Hasil CT Scan thorax dengan kontras menunjukkan adanya massa solid pada cavum pleura kanan yang menginfiltrasi otot dinding dada di sekitarnya, pneumonia bilateral, serta lesi osteolitik pada tulang belakang yang dicurigai sebagai suatu proses metastase atau penyebaran keganasan. Hasil biopsi menunjukkan gambaran morfologi sebaran difus sel plasma imatur-matur dengan pendekatan pada diagnosis cutaneus infiltration plasma cell myeloma dengan diagnosis banding plasmablastic lymphoma.Simpulan: Hasil pencitraan rontgen dan CT scan thorax membantu menyempitkan diagnosis banding, di mana terdapat gambaran tumor pada dinding dada dengan destruksi tulang dan jaringan lunak di sekitarnya serta gambaran infiltrasi ke pleura disertai gambaran osteolitik multipel pada vertebrae. Dibantu dengan pemeriksaan biopsi (patologi anatomi)  maka diagnosis yang paling mendekati pada pasien ini adalah plasma cell myeloma dinding dada